ONLINE LEARNING (DARING) DURING THE COVID-19 PANDEMIC IN THE STKIP PESISIR SELATAN GEOGRAPHY EDUCATION STUDY PROGRAM - Veni Veni; Riri Lestari; Muhammad Arif (Tunas Geografi, 2021)
Online lectures are a learning process utilizing information technology, utilizing the internet as a method of delivery, interaction and facilitation. This study aims to see how the implementation of online learning during the covid-19 pandemic, the perceptions of lecturers and students towards online learning, the obstacles faced during online learning in the Geography Education Study Program. The research is descriptive qualitative. Research respondents are lecturers who teach at the Geography Education Program as many as 12 people and 22 students. Data were collected through google forms and interviews. The results showed that learning was carried out online and face-to-face using the google meet application, zoom meeting, google classroom and whatsapp group, the use of the application according to respondents was easy, respectively 83.3% and 63.6%. The devices used, 83% lecturers use laptops and 53.8% use smartphones, 100% of students use smartphones and 31.8% use laptops. Online learning methods are quite diverse, face-toface through applications, giving materials and assignments, presentations by students individually/groups and application discussion forums. Based on the results of student interviews, it was quite difficult to understand the material, online learning (online) was not effective due to obstacles during online lectures, but 63.6% of students were quite satisfied and 83.3% of lecturers also stated that they were quite satisfied with the online lectures they had carried out. The obstacles that arise during online learning are generally the limitations of the internet network and internet quota.